Prevalence and Correlates of Self-Harm in the German General Population. - Astrid Müller; Laurence Claes; Dirk Smits; Elmar Brähler; Martina de Zwaan (PLoS ONE, 2016)
The study aimed at evaluating the psychometric properties of the German version of the Self- Harm Inventory (SHI) and examining the lifetime prevalence and correlates of self-harm in a representative German population sample (N = 2,507; age mean = 48.79, SD = 18.11; range 14 to 94 years; 55.5% women) using the SHI. All participants answered the German SHI, the short form of the Barratt Impulsiveness Scale (BIS-15), the ultra-brief Patient Health Questionnaire for Depression and Anxiety (PHQ-4), and provided sociodemographic information. The one-factorial structure of the SHI was replicated using a confirmatory factor analysis. Internal consistency coefficients were sufficient and in line with previous studies. Almost half of the sample (49%) acknowledged at least one self-harming behavior over the life-span, most frequently indirect forms of self-harm. The rate of participants who engaged in at least one SHI behavior was higher among men than women (51.6% vs. 46.9%, respectively, χ2 = 5.38, p = 0.020). Higher SHI scores were related to younger age, male gender, living alone, more symptoms of anxiety and depression (PHQ-4), higher impulsivity scores (BIS-15), and suffering from obesity grade 2. Women engaged more often in discreet forms of self-harm than men, e.g., preventing wounds from healing, exercising an injury, starving, and abusing laxatives. In terms of other indirect self-harming behaviors, men admitted more often driving recklessly, being promiscuous and losing a job on purpose, while women reported more frequently engaging in emotionally abusive relationships. With respect to direct self-harm, women were more likely to endorse suicide attempts and cutting, while men admitted more often head-banging. The findings suggest that self-harm constitutes a common problem. Future longitudinal studies are required to examine the natural course, sociodemographic and psychopathological risk factors, as well as possible time-trends of self-harming behaviors in more depth.